Adaptive Routing Update Approach for VANET using Local Neighbourhood Change Information - Rasheed, Asim; Ajmal, Sana; Qayyum, Amir (Malaysian Journal of Computer Science, 2014)
The recent advancements in the field of wireless communication have enabled some wireless networks to become of highly dynamic in nature, like Vehicular Ad hoc Networks (VANETs). This emergence of specialised networks involves high relative node velocity and high active node density. Such complexities demand more efficient and intelligent routing techniques. Anefficient routing algorithmfinds thebest possible route with minimum overhead, updatesiton availability of a better one and then maintainsroutein case of link breakages. Many routing protocols focus on finding and maintaining efficient routes, whereas very less emphasis is put on route update. We have evaluated some existing route updating techniques, which are based on periodic, event triggered or flow based routing information sharing schemes. The evaluation shows that current routing metric sharing schemes do not perform well under varying network scenarios. Subsequently, a model is proposed for adaptive route update of dynamic networks. From theoretical analysis and simulation, the results show that the proposed adaptive route update approach is applicable to a number of routing strategies. The proposed adaptive strategy for routing information sharing is not restricted to any specific routing approach and can enhance the efficiency of routing protocols in varying network conditions.